2021
DOI: 10.1001/jamanetworkopen.2020.37199
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi or Exercise on Sleep in Older Adults With Insomnia

Abstract: IMPORTANCE Previous studies that have shown tai chi to improve sleep were mainly based on subjective assessments, which might have produced results confounded by self-reporting bias. OBJECTIVE To compare the effectiveness of tai chi for improving sleep in older adults with insomnia with conventional exercise and a passive control group using actigraphy-based objective measurements. DESIGN, SETTING, AND PARTICIPANTS This randomized, 3-arm, parallel group, assessor-masked clinical trial was conducted at a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 30 publications
3
69
1
2
Order By: Relevance
“…In line with the existing data, we demonstrated that the two exercise modalities could attenuate depression and anxiety scores in HADS. The beneficial effects of conventional exercise and Tai Chi on sleep is also well documented 55 . Our observation that neither intervention led to improved sleep quality may be due to the low baseline PSQI scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the existing data, we demonstrated that the two exercise modalities could attenuate depression and anxiety scores in HADS. The beneficial effects of conventional exercise and Tai Chi on sleep is also well documented 55 . Our observation that neither intervention led to improved sleep quality may be due to the low baseline PSQI scores.…”
Section: Discussionmentioning
confidence: 99%
“…A significant group-by-time interaction indicated a difference in the intervention-mediated changes among interventions by time. Pairwise comparisons with baseline adjustment were then performed with R package “multcomp” using a closed test procedure with Bonferroni-Holm correction 54 , 55 . Statistical significance was considered at P < 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…In consideration of the observed global decline in exercise training during the social distancing measures ( Fibit, 2020 ) and the well-documented beneficial effects of exercise as an affordable, non-invasive intervention to treat and prevent depressive symptoms, anxiety ( Carek et al, 2011 ; Craft and Perna, 2004 ) and poor sleep quality ( Siu et al, 2021 ), our main objective was to investigate associations between exercise training and mental health outcomes. We expected individuals who were able to keep their exercise routines at a stable level or even increased their exercise volume to show less symptoms of depression, anxiety and sleep problems, whereas individuals whose inactivity increased to exhibit higher levels of mental distress.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, the prevalence of sleep problems in TCM universities is significantly lower than that in Western medical universities, probably because TCM students are better at adjusting life schedules according to their specialized courses. The courses in TCM universities involve acupuncture, massage, Qigong ( 49 ), Tai Chi ( 50 ), Chinese herbs, and so forth. TCM students practice iteratively for training, and they often apply these treatments to each other to help solve physical problems.…”
Section: Discussionmentioning
confidence: 99%